Does Free Shipping Affect Purchasing Decisions in E-commerce in Indonesia? - Rabbani, Maheswara; Hermawan, Jeremy Hermon; Utomo, Kawang; Gunawan, Raveldy Guinzy; Wijaya, Theresa Karyn (The Indonesian Journal of Computer Science, 2023)
The trend of buying and selling goods online using e-commerce platforms has become part of the lifestyle of Indonesian people in recent years. E-commerce business people prepare ways or strategies so users can feel enthusiastic when shopping. However, shipping costs are one of the primary considerations for users before making payments. Users are required to spend more than the price of the goods to pay for the shipping costs. Meanwhile, not all users are willing to pay for shipping costs because they don't save on spending costs. This study aims to understand whether someone's purchase decision in e-commerce is influenced by free shipping. The study's results reveal that free shipping costs affect a person's purchasing decision to buy goods online in e-commerce. In addition, there are four other factors that influence purchasing decisions in e-commerce, namely product completeness, price variation, cashback promo, and ease of use.